Incessant Atrio‐Ventricular Node Reentrant Tachycardia Induced by Unapparent Dual Atrio‐Ventricular Node Conduction. Issue 4 (3rd May 2012) - MAURY, PHILIPPE; DETIS, NICOLAS; DUPARC, ALEXANDRE; MONDOLY, PIERRE; ROLLIN, ANNE; DELAY, MARC
<x xml:space="preserve">Abstract</x> We present the case of a patient with incessant slow‐fast atrio‐ventricular (AV) node reentrant tachycardia induced by dual AV node conduction with aborted conduction to the ventricles. The unapparent conduction over the slow pathway was suspected here because of spontaneous nodal echoes without QRS complexes occurring during sinus rhythm, manifested as isolated premature atrial beats and which repetitively induced the tachycardia.